Vibration of a rectangular plate with a central power-law profiled groove by the Rayleigh–Ritz method. (March 2016) - O'Boy, D.J.; Krylov, V.V.
Abstract: The prediction of natural frequencies of rectangular plates where a profiled indentation is present is made using a Rayleigh–Ritz variational energy method. Panels with holes are often found for access cables and access gaps, and it is shown that the application of damping to the profile leads to a more efficient method of reducing vibration than covering a whole rectangular plate, which is advantageous where weight saving is necessary.